Infiltration Characteristics of Soils Under Different Soil Series of Jumar Nala Sub-watershed - Baxla, A K; Kumar, Ramesh; Wadood, A (Annals of Arid Zone, 2016)
Infiltration characteristics of Ultic Baleustalf, Ultic Paleustalf, Udic Haplastalf and Typic Haplaquent soils, falling under Nagri, Kokdro, Barhu and Bukru soil series, respectively of Jumar nala sub-watershed, Ranchi, were studied. The upland soil series, Nagri and Kokdro, exhibited higher infiltration rates (4.8 and 6.2 cm h'I) as compared to that in Barhu (4.0 cm hÂ·I) and Bukru (2.8 cm hÂ·l) soil series representing midland and lowland topography, respectively. Cumulative infiltration also followed the similar trend among the series. Texture, bulk density and geometric mean diameter (GMD) of aggregates supported the above findings. The deviation between the observed and predicted values of cumulative infiltration was 0.824, 0.075, 0.865 and -0.639% in soil series Kokdro, Nagri, Barhu and Bukru, respectively.